1982
DOI: 10.1146/annurev.nu.02.070182.000321
|View full text |Cite
|
Sign up to set email alerts
|

Liver Disease and Protein Needs

Abstract: Protein deficiency is often associated with liver disease. The principal cause of protein deficiency is decreased dietary intake. Deficiencies in digestion and absorption that are common in alcoholics contribute to protein deficiency in alcoholic liver disease. The protein requirements in most patients with compensated chronic liver disease are not different from normal, but increase during episodes of hepatocellular deterioration. An increased demand for protein after liver injury drains nitrogen from other o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 143 publications
(144 reference statements)
1
22
0
Order By: Relevance
“…These decreased serum levels in the face of high liver levels of retinoids are not due to malabsorption or retinoid de"ciency but due to decreased mobilization of retinoids from the liver (Mezey, 1982). Decreased mobilization may be due in part to the known inhibitory e!ect of increased retinoic acid levels on the hepatic secretion of RBP (Keilson et al, 1979;Barua et al, 1997).…”
Section: Retinoid Concentrations Increase In Livermentioning
confidence: 99%
See 1 more Smart Citation
“…These decreased serum levels in the face of high liver levels of retinoids are not due to malabsorption or retinoid de"ciency but due to decreased mobilization of retinoids from the liver (Mezey, 1982). Decreased mobilization may be due in part to the known inhibitory e!ect of increased retinoic acid levels on the hepatic secretion of RBP (Keilson et al, 1979;Barua et al, 1997).…”
Section: Retinoid Concentrations Increase In Livermentioning
confidence: 99%
“…Retinoid intoxication is also associated with dry skin and alopecia which, however, are not seen typically in PBC. Splenomegaly and 50 (Bodenheimer, 1995;Sherlock, 1994;Mezey, 1982).…”
Section: Retinoid Toxicity and Pbc: Parallel Signs Symptoms And Labomentioning
confidence: 99%
“…This can only imply that the damage to the liver may not have taken a chronic course as to impair the protein synthetic function of the liver. Researchers have reported that such functions like protein production can be affected in the cases of chronic hepatic impairment (Mezey, 1982). The plasma half-life of plasma proteins is 2-3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of infective hepatitis, the RBP-prealbumin complex and plasma vitamin A were decreased in association with reduced hepatic mobilization and very high liver levels of vitamin A, resulting in a mixed symptom pattern of hypo-and hypervitaminosis A [202].…”
Section: Outline Of the Model (1) Viral-speci�c Cd8mentioning
confidence: 99%